2007
DOI: 10.1007/s11538-007-9251-8
|View full text |Cite
|
Sign up to set email alerts
|

How Host Population Dynamics Translate into Time-Lagged Prevalence: An Investigation of Sin Nombre Virus in Deer Mice

Abstract: Human cases of hantavirus pulmonary syndrome caused by Sin Nombre virus are the endpoint of complex ecological cascade from weather conditions, population dynamics of deer mice, to prevalence of SNV in deer mice. Using population trajectories from the literature and mathematical modeling, we analyze the time lag between deer mouse population peaks and peaks in SNV antibody prevalence in deer mice. Because the virus is not transmitted vertically, rapid population growth can lead initially to reduced prevalence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 44 publications
3
49
0
Order By: Relevance
“…Similar results have also been reported from other hantavirushost systems (Calisher et al 1999(Calisher et al , 2005Douglass et al 2001). A high influx of newborns during the breeding season may decrease hantavirus prevalence, and this 'juvenile dilution effect' has been proposed to be the mechanism through which the expected positive relationship between prevalence and abundance is lacking or delayed Davis et al 2005;Adler et al 2008).…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar results have also been reported from other hantavirushost systems (Calisher et al 1999(Calisher et al , 2005Douglass et al 2001). A high influx of newborns during the breeding season may decrease hantavirus prevalence, and this 'juvenile dilution effect' has been proposed to be the mechanism through which the expected positive relationship between prevalence and abundance is lacking or delayed Davis et al 2005;Adler et al 2008).…”
Section: Introductionsupporting
confidence: 82%
“…During the breeding season, there was naturally an influx of young uninfected individuals. The decrease in hantavirus prevalence over a breeding season has generally been attributed to this influx Davis et al 2005;Adler et al 2008), and the seasonal variation in PUUV prevalence observed here and previously (Verhagen et al 1986;Escutenaire et al 2000;Sauvage et al 2002) may in part be caused by such a juvenile dilution effect . But it may often not be the whole story.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, the density-dependent relationship is not completely clear due to confounding effects that occur during periods of rapid population growth. During periods of rapid population growth, the lack of vertical transmission leads to a dilution of susceptible rodents and reduced prevalence Adler et al 2008).…”
Section: Introductionmentioning
confidence: 99%